\(\Leftrightarrow\left(x^2+2x\right)^2-2\left(x^2+2x\right)-3=0\)
\(\Leftrightarrow\left(x^2+2x-3\right)\left(x^2+2x+1\right)=0\)
\(\Leftrightarrow\left(x+3\right)\left(x-1\right)\left(x+1\right)^2=0\)
hay \(x\in\left\{-3;1;-1\right\}\)
\(\Leftrightarrow\left(x^2+2x\right)^2-2\left(x^2+2x\right)-3=0\)
\(\Leftrightarrow\left(x^2+2x-3\right)\left(x^2+2x+1\right)=0\)
\(\Leftrightarrow\left(x+3\right)\left(x-1\right)\left(x+1\right)^2=0\)
hay \(x\in\left\{-3;1;-1\right\}\)
Tính (rút gọn )
1, 2x(3x-1)-(2x+1)(x-3)
2, 3(x^2-2x)-(4x+2)(x-1)
3, 3x(x-5)-(x-2)^2 -(2x+3)(2x-3)
4, (2x-3)^2+(2x-1) (x+4)
làm phép chia :
a) (x^4 -2x^3 + 2x -1) : (x^2 - 1)
b) (x^3 -8) : (x^2 + 2x +4)
c) (x^6 - 2x^5 + 2x^4 + 6x^3 - 4x^2)n: 6x^2
d) (-2x^5 + 3x^2 - 4x^3) :2x^2
e) (15x^3 - 10x^2 + x - 2) : (x - 2)
f) (2x^4 - 3x^3 - 3x^2 + 6x - 2) : (x^2 - 2)
Tìm x
(2x-3).(x+1)-2x^2+6x=0
(X^2-x+1).(x-3)-x^3+4x^2=0
(X^2-2).(x^2+2)-x^4-2x+5=0
(X-3).(x^2-3x+2)-(x^2-2x-7).(x-2)+2x^2-2x=0
P)(9-x)(x^2+2x-3) n)(-x+3)(x^2+x+1) O)(-6x+1/2)(x^2-4x+2) q)(6x+1)(x^2-2x-3) r)(2x+1)(-x^2-3x+1) U)(2x-3)(-x^2+x+6) s)(-4x+5)(x^2+3x-2) V)(-1/2x+3)(2x+6-4x^3)
1.giải phương trình :
1)1 + 2/x-1 + 1/x+3=x^2+2x-7/x^2+2x-3
2)x/x^2+5x+6=2/x^2+3x+2 (x=3)
3)1/x^2+9x+20 - 1/x^2+8x+12=x^2-2x-33/x^2+8x+15 (x=-5,7)
4)x+5/3x-6 - 1/2=2x-3/2x-4 (x=25/7)
5)x-1/x^3+1 + 2x+3/x^2-x+1=2x+4/x+1 - 2(x=0)
thực hiện phép tính
1)2x^2(-3x^2+2x-1)
2)(x-3)(x+7)-(x+5)(x-1)
3)-2x(-3x+2)-(x+2)^2
4)(2x-3)(x^2-2x-4)
a)(3x-1)2+2(3x-1)(2x+1)(2x+1)2
b)(x2+1)(x-3)-(x-3)(x2+3x+9)
c)(2x+3)2+(2x+5)2-2(2x+3)(2x+5)
d)(x-3)(x+3)-(x-3)2
e)(2x+1)2+2(4x2-1)+(2x-1)2
f)(x2-1)(x+2)-(x-2)(x2+2x+4)
a)(3x-1)2+2(3x-1)(2x+1)(2x+1)2
b)(x2+1)(x-3)-(x-3)(x2+3x+9)
c)(2x+3)2+(2x+5)2-2(2x+3)(2x+5)
d)(x-3)(x+3)-(x-3)2
e)(2x+1)2+2(4x2-1)+(2x-1)2
f)(x2-1)(x+2)-(x-2)(x2+2x+4)
Khai triển và thu gọn:
1, x(3x - 1) - 2x(x - 1) - (x - 2)2
2, x(2 + x) - (x - 1)(3 - x)-(3 - x)2
3, (2x - 1)2 - 2(2x - 1)(2x - 3) + (3 - 2x)2
giải phương trình sau
1/ 2x( x+3) - 6 (x-3) =0
2/ 2x^2( 2x+3) +(2x+3) =0
3/ (x-2) (x+1) -(x-2) 4x =0
4/ 2x ( x-5) -3x +15=0
5/ 3x(x+4) -2x-8 =0
6/ x^2 (2x-6) + 2x -6 =0